Muggie Maggie - Cleary, Beverly; Life, Kay (New York : Avon Books, 1991)
Maggie resists learning cursive writing in the third grade, until she discovers that knowing how to read and write cursive promises to open up an entirely new world of knowledge for her.
"An Avon Camelot Book."
730
Keywords: Penmanship -- Juvenile fiction; Schools -- Juvenile fiction; Penmanship -- Fiction; Schools -- Fiction